Thrips Management Program for Horticultural Crops - Vivek Kumar; Garima Kakkar; Cristi L. Palmer; Cindy L. McKenzie; Lance S. Osborne (EDIS)
Among the 5,500 (or more) well-described species of thrips worldwide, nearly 1% are known as economically important pests. Because these tiny pests can feed on multiple plants, their damage potential to nursery and greenhouse production is immense: thrips inflict millions of dollars loss every year. Thrips hide easily in tiny spaces, reproduce rapidly, and can survive in a lot of climates. And they are invisibly small! Thrips infestations present a huge problem in the regional and international trade of plant materials and products, due to the quarantine risks and damage associated with several species in the order.